The role of attribution in weight anxiety and eating disorders in women - Bennett, Kate Mary (1993)
This thesis examines weight anxiety and eating disorders amongst women from an attributional perspective. The studies comprise two distinct but interrelated components: investigations of the role of attribution in the development and maintenance of weight anxiety and eating disorders; and analyses of two screening instruments for eating disorders. The study presented in Chapter 2 examines whether, amongst women without an eating disorder, attributions can be extracted in a factor-analytic manner to form relevant stereotypes associated with 'fat' or 'thin' women. The results confirm that clear weight-related factors can be extracted, and these resemble common stereotypes of fatness and thinness. In Chapters 3 and 4 the attributions of both eating disordered and non-eating disordered women were examined. Four groups have been examined: the Anorexic group; the Bulimic group; the Over-Eater group; and the Non-Eating Disordered group.